Survivorship of the Bernese Periacetabular Osteotomy: What Factors are Associated with Long‐term Failure?. Issue 2 (February 2017) - Wells, Joel; Millis, Michael; Kim, Young‐Jo; Bulat, Evgeny; Miller, Patricia; Matheney, Travis
Abstract: Background: The Bernese periacetabular osteotomy (PAO) continues to be a commonly performed nonarthroplasty option to treat symptomatic developmental hip dysplasia, but there are few long‐term followup studies evaluating results after PAO. Questions/purposes: (1) What is the long‐term survivorship of the hip after PAO? (2) What were the validated outcomes scores among patients who had PAO more than 14 years ago? (3) What factors are associated with long‐term failure? Methods: One hundred fifty‐eight dysplastic hips (133 patients) underwent PAO between May 1991 and September 1998 by a single surgeon. Of those, 37 hips (34 patients [26%]) were lost to followup; an additional seven patients (5% [eight hips]) had not been seen in the last 5 years. The 121 hips (in 99 patients) were retrospectively evaluated at a mean of 18 years (range, 14‐22 years). Survivorship was assessed using Kaplan‐Meier analysis with total hip arthroplasty (THA) as the endpoint. Hips were evaluated for activity, pain, and general health using the UCLA Activity Score, modified Harris hip score, WOMAC, and Hip disability and Osteoarthritis Outcome Score (HOOS). Failure was defined as a WOMAC pain subscale score ≥ 10 or having undergone THA. Hips were divided into three groups: asymptomatic (did not meet any failure criteria at any point in time), symptomatic (met WOMAC pain failure criteria at previous or most recent followup), and replaced (having undergone THA). A multinomial logistic regression model using a general estimating equations approach was used to assess factors associated with failure. Results: Kaplan‐Meier analysis with THA as the endpoint revealed a survival rate (95% confidence interval [CI]) of 74% (66%‐83%) at 18 years. Twenty‐six hips (21%) underwent THA at an average of 9 ± 5 years from the surgery. Sixty‐four hips (53%) remained asymptomatic and did not meet any failure criteria at most recent followup. Thirty‐one hips (26%) were symptomatic and considered failed based on a WOMAC pain score of ≥ 10 with a mean ± SD of 11 ± 4 out of 20 at most recent followup. Although some failed initially by pain, their most recent WOMAC score may have been < 10. Of the 16 symptomatic hips that failed early by pain (reported a WOMAC pain subscale score ≥ 10 in the prior study), two were lost to followup, two underwent THA at 16 and 17 years, four still failed because of pain at most recent followup, and the remaining eight had WOMAC pain scores < 10 at most recent followup. Asymptomatic hips reported better UCLA Activity Scores (asymptomatic: mean ± SD, 7 ± 2; symptomatic: 6 ± 2, p = 0.001), modified Harris hip scores (pain, function, and activity sections; asymptomatic: 80 ± 11; symptomatic: 50 ± 15, p < 0.001), WOMAC (asymptomatic: 2 ± 2, symptomatic: 11 ± 4, p < 0.001), and HOOS (asymptomatic: 87 ± 11, symptomatic: 52 ± 20, p < 0.001) compared with symptomatic hips at long‐term followup. Age older than 25 years at the time of PAO (symptomatic: odds ratio [OR], 3.6; 95% CI, 1.3‐9.8; p = 0.01; replaced: OR, 8.9; 95% CI, 2.6‐30.9; p < 0.001) and a preoperative joint space width ≤ 2 mm (replaced: OR, 0.3; 95% CI, 0.12‐0.71; p = 0.007) or ≥ 5 mm (replaced: OR, 0.121; 95% CI, 0.03‐0.56; p = 0.007) were associated with long‐term failure while controlling for poor or fair preoperative joint congruency. Conclusions: This study demonstrates the durability of the Bernese PAO at long‐term followup. In a subset of patients, there was progression to failure over time. Factors of progression to THA or more severe symptoms include age older than 25 years, poor or fair preoperative hip congruency, and a preoperative joint space width that is less than 2 mm or more than 5 mm. Future studies should focus on evaluating the two failure groups that we have identified in our study: those that failed early and went on to THA and those that are symptomatic at long‐term followup. Level of Evidence: Level III, therapeutic study.